Perancangan Kursi Eceng Gondok Dengan Rangka Besi - Ivana, Marietta; Setiawan, Andereas Pandu; Poillot, Jean Francois (Intra, 2019)
Water hyacinth has been found in Indonesian waters, such as rivers, rivers and many more. Water hyacinth often referred as water pollutants because plenty of amount due to rapid reproduction. Water hyacinth is also considered an unprofitable plant. These problems actually have a solution, which is by utilizing water hyacinth in various fields, one of the example is product material. The design that I want to build in this final project is the design of interior furniture products, which is a chair that can be beneficial for the environment because it utilizes existing natural resources, water hyacinth, with iron as the frame. This design aims to help reduce water pollution while creating a traditional yet modern minimalist design with water hyacinth and iron as the material. The design method that I carried out was a qualitative method, which is design thinking: emphatize, observe, ideate, prototype, and test. I hope this design can help reduce water pollution and turn it into something beautiful and beneficial for the interior world.